Korespondencja (1941)
Listy od następujących: Iłłakowiczówna Kazimiera 1948-1967 (29) k. 1-38. - Immaculata urszulanka 1968 (1) k. 39. - Indelmann, Mojżesz 1941 (1) k. 40. - Ingarden Roman 1957-1958 (2) k. 41-42.
Mf 11059